Optimizing Arabic Language Learning for Students with Disabilities through Artificial Intelligence in Distance Education: تحسين تعلُّم اللغة العربية للطلاب ذوي الإعاقة من خلال الذكاء الاصطناعي في التعليم عن بُعد - Muhammad Zaairul Haq; Faisol Nasar Bin Madi; Syamsul Anam (Universitas Islam Negeri Palangka Raya, 2025)
This study addresses the empirical gap in research on the integration of Artificial Intelligence (AI) in learning Arabic for students with disabilities within Distance Learning contexts. To bridge this literature gap, the study examines the effectiveness of AI in enhancing Arabic language comprehension. Using a qualitative approach involving observation, interviews, and assessments, it evaluates improvements in vocabulary mastery, sentence structure understanding, and learner engagement. The implementation of AI features such as text-to-speech technology, interactive chatbots, and automated feedback demonstrated significant results in vocabulary retention and learning enthusiasm. However, technical challenges were identified, including unstable internet connectivity and interface accessibility issues for students with physical disabilities. The findings confirm the strategic potential of AI as an inclusive learning tool while recommending the development of more accessible platforms. Further research is needed to refine the effectiveness and accessibility of AI tools in Distance Learning for learners with disabilities.